Changes in Finland's international investment position, 1985-1998: A brief statistical analysis - Jorma Hilpinen; Heikki Hella (Bank of Finland, 1999)
This paper attempts to describe and compare developments in the components of Finland's net international investment position (NIIP).The data consist of sectoral flows and valuation items over the period 1985 - 1998, which is, for analytical purposes, broken down into two subperiods: before and after the Finnish markka was floated.The study focuses on the main sectors, ie banks, corporations and the central government.Valuation items (changes in exchange rates and equity prices) are also important in the decomposition of the NIIP, particularly as regards recent history of equity prices.The mean and variability of each item is estimated, and for some items also bivariate robust variance tests are carried out. The major feature in Finland's balance of payments has been nonresidents' increased interest in Finnish equities as an object of investment.This phenomenon, along with the boom in share prices, has in recent years raised the equity holdings of foreigners to the rank of most significant item in Finland's international investment position.Another important feature in the BOP is the rapid growth of the central government's foreign debt due to the deep recession of 1991 - 1994.In respect to Finland, it is important to note the different stories told by developments in NIIP vs net external debt components: NIIP figures indicate that ownership of corporations based in Finland has indeed become global and that the value of shares has been increasing, whereas net external debt figures indicate that the economy has succeeded in restoring external indebtedness to pre-recession levels. The results also confirm that the Finnish banks still contribute prominently to variations in Finnish BOP flows.As regards the late 1980s and early 1990s, this can be inferred from the highly bank-oriented structure of Finnish financial markets, but the same holds true during the 1990s as well in the period of recovery from economic crisis.
URN:NBN:fi:bof-20140807178
Keywords: 330